SEMI GUIDED INQUIRY LEARNING MODEL WITH DEMONSTRATION-EXPERIMENTS METHOD TO TRAIN ELEVENTH GRADE STUDENT’S CREATIVITY ON REACTION RATES MATTER (Universitas Negeri Surabaya, 2017)
The implementation of this research which used quasi experimental with One group pretest posttest design was aimed to describe the students creativite thinking skills to the implementation of semi guided inquiry learning model with demonstration-experiments method on reaction rates matter. From all of students in the MIA of the 11th grade in SMAN 1 Sidoarjo on the odd semester 2016-2017 academic year was obtained the MIA 4 of the eleventh grade as a sample. The method used in this research were observation and test. The instrument used in this research were students activity observation sheet, and the creativite thinking skills test. The results showed that the students creative thinking skills has been practice proven by posttest score of students creative thinking skills have reached the determined score ≥ 3. Students latest creative thinking skills obtained a total of 2 students or by 6,25% scored 3 (B), a total of 17 sudents or by 53,12% scored 3,20-3,50 (B+), a total of 11 students or by 34,38% scored 3,60-3,80 (A-), and a total of 2 students or by 6,25% scored 4 (A). Keywords: semi guided inquiry, demonstration, experiment , creativity, creative thingking skill.